1995
DOI: 10.1128/iai.63.10.3966-3972.1995
|View full text |Cite
|
Sign up to set email alerts
|

A novel costimulatory factor for gamma interferon induction found in the livers of mice causes endotoxic shock

Abstract: Administration of monoclonal anti-CD3 antibody to mice treated with Propionibacterium acnes induced secretion of a high level of gamma interferon (IFN-␥) into the circulation system, while it induced no significant release in untreated mice. In order to analyze this high-level induction of IFN-␥ in these bacterium-treated mice, we investigated the factors that might be involved. An activity that induces IFN-␥ in T cells was observed in the liver extracts of mice treated with P. acnes and subsequently challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(96 citation statements)
references
References 25 publications
3
89
0
1
Order By: Relevance
“…First, Exo/IL-18 can chemoattract DC and T cells and thus potentially accumulate these immune cells locally at the sites of administration [16,17]. Secondly, IL-18 contained in Exo/IL-18 may induce the release of IFN-γ, leading to the final elimination of tumor cells [8][9][10][11][12][13]. Thirdly, IL-18 augments the release of IL-2 and promotes T cell proliferation [43], supporting the idea that immune molecules such as IL-18, IFN-γ and IL-2 can influence the local environment in a way that would be beneficial for the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Exo/IL-18 can chemoattract DC and T cells and thus potentially accumulate these immune cells locally at the sites of administration [16,17]. Secondly, IL-18 contained in Exo/IL-18 may induce the release of IFN-γ, leading to the final elimination of tumor cells [8][9][10][11][12][13]. Thirdly, IL-18 augments the release of IL-2 and promotes T cell proliferation [43], supporting the idea that immune molecules such as IL-18, IFN-γ and IL-2 can influence the local environment in a way that would be beneficial for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18, previously identified as IFN-γ-inducing factor, is also a promising vaccine adjuvant [8]. IL-18 elicits a variety of effects on immune response, including stimulating natural killer cells (NK) and T/B lymphocytes to produce high levels of IFN-γ and IL-2 [8,9], promoting T cell proliferation [8,10], enhancing killing activity of cytotoxic T lymphocytes (CTL) and NK cells [11][12][13], facilitating DC maturation [14], exerting pro-inflammatory properties by inducing the release of IL-1β, TNF-α, chemokines [15] and chemoattracting DC, T cells and polymorphonuclear cells [16][17][18]. We and others have previously shown that IL-18 has potent anti-tumor immunity by inducing CD4 + , cytotoxic CD8 + T cells and NK cells [12,13,[19][20][21][22][23], potentiating FasLmediated cytotoxicity and inhibiting tumor angiogenesis [12,24].…”
Section: Introductionmentioning
confidence: 99%
“…IL-18 is a classical inducer of IFN-γ, the defining cytokine of Th1 CD4 + T cells (Harrison et al, 2015;Okamura et al, 1995;Robinson et al, 1997;Smeltz, Chen, Hu-Li, & Shevach, 2001). In response to various microbial stimuli, IEC-derived IL-18 may act on Th17 and regulatory CD4 + T cell (Treg) populations, in addition to Th1 cells (Chudnovskiy et al, 2016;Harrison et al, 2015;Smeltz et al, 2001).…”
Section: Il-18 Acts On Cd4 + T Cell Populationsmentioning
confidence: 99%
“…Because other cytokines can act as co-stimulants for IFN-␥ production, the failure of neutralizing antibodies to IL-1, IL-4, IL-5, IL-6, or TNF to neutralize the serum activity suggested that it was a distinct factor. In 1995, the third report was published from the same scientists demonstrating that the endotoxin-induced costimulant for IFN-␥ production was present in extracts of livers from mice preconditioned with P. acnes [22]. In this model, the hepatic macrophage population (Kupffer cells) expands dramatically, and in these mice a low dose of bacterial lipopolysaccharide (LPS), which in non-preconditioned mice is not lethal, becomes lethal.…”
Section: Discovery Of Ifn-␥ Inducing Factormentioning
confidence: 99%